Emergency Neuro-ophthalmology Rapid Case Demonstration - Wang, An-Guor (Springer Singapore, 2018)
This book presents 57 typical cases of neuro-ophthalmic diseases in the emergency room, which represent notoriously complex and difficult challenges for junior doctors. The physical manifestations of these neurologic disorders include visual loss, transient blurring, diplopia, headache, pupillary abnormality, and even cognition problems. Each case provides a wealth of information, including the case report, comments, diagnosis, management, prognosis and concise notes, as well as photographs and other images. As a case-based clinical reference work on neuro-ophthalmic diseases, the book offers readers essential, concretely applicable information and guidance. An-Guor Wang is an associate professor at the Department of Ophthalmology and director of the Neuro-ophthalmology & Strabismus Section, Department of Ophthalmology, Taipei Veterans General Hospital, National Yang-Ming University, Taipei, Taiwan.